Machine Learning and Data Science for Process Industries - Dube, Yejur; Soni, Vinamra; Kumar, J. Satheesh (Journal of Soft Computing Paradigm, 2022)
In the last few years, Machine Learning has drawn a lot of attention. One of the reasons it is getting popular today is that, it provides a united domain for dealing with problems with intelligent-decision making skills. From small to big firms, Machine Learning is now used to extract the best data models which ultimately benefits the company. This paper lays the foundation of a thorough investigation of the machine learning world and study what exactly is the reason behind the huge surge of this new phenomenon in the industry today. Moreover, it discusses the use of Data Science, improvements in several leading industries, some case studies and the impact of its growth in usage in the world today. Based on many graphs and business models, why and how some leading companies are incorporating Machine Learning and Data Science in their business plans and whether it has benefitted them in the long run, have been analysed.
Keywords: Data science; machine learning; neural networks; process industries